p.Arg1809Cys substitution in neurofibromin is associated with a distinctive NF1 phenotype without neurofibromas - Pinna, Valentina; Lanari, Valentina; Daniele, Paola; Consoli, Federica; Agolini, Emanuele; Margiotti, Katia; Bottillo, Irene; Torrente, Isabella; Bruselles, Alessandro; Fusilli, Caterina; Ficcadenti, Anna; Bargiacchi, Sara; et al. (European journal of human genetics : EJHG, 2015)
Analysis of 786 NF1 mutation-positive subjects with clinical diagnosis of neurofibromatosis type 1 (NF1) allowed to identify the heterozygous c.5425C>T missense variant (p.Arg1809Cys) in six (0.7%) unrelated probands (three familial and three sporadic cases), all exhibiting a mild form of disease. Detailed clinical characterization of these subjects and other eight affected relatives showed that all individuals had multiple cafè-au-lait spots, frequently associated with skinfold freckling, but absence of discrete cutaneous or plexiform neurofibromas, Lisch nodules, typical NF1 osseous lesions or symptomatic optic gliomas. Facial features in half of the individuals were suggestive of Noonan syndrome. Our finding and revision of the literature consistently indicate that the c.5425C>T change is associated with a distinctive, mild form of NF1, providing new data with direct impact on genetic counseling and patient management.